2014
DOI: 10.5539/jas.v6n2p119
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Supplemental Irrigation and Graded Levels of Nitrogen on Cotton Yield and Quality

Abstract: Effects of supplemental irrigation and graded levels of nitrogen (N) on cotton yield and fiber quality were investigated in the Mississippi Delta in 2011 and 2012. Cotton was planted in 48 experimental plots with irrigation as main treatment unit and N application rate (0, 39, 67, 101, 135, and 168 kg ha -1 ) as subunit. Supplemental irrigation was conducted based on soil-water sensor measurements. Cotton yield was determined using a boll buggy equipped with load cells. Cotton samples were collected and ginned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 10 publications
0
8
0
1
Order By: Relevance
“…Esse comportamento também foi observado por outros autores, como Wen et al (2013) e Dagdelen et al (2009), que afirmam que muitas características de qualidade das fibras são influenciadas diretamente por variáveis ambientais, como o estresse hídrico. Autores como Sui et al (2014) e Balkcom et al (2006) afirmam que o aumento da irrigação implica em aumento no comprimento da fibra.…”
Section: Resultsunclassified
“…Esse comportamento também foi observado por outros autores, como Wen et al (2013) e Dagdelen et al (2009), que afirmam que muitas características de qualidade das fibras são influenciadas diretamente por variáveis ambientais, como o estresse hídrico. Autores como Sui et al (2014) e Balkcom et al (2006) afirmam que o aumento da irrigação implica em aumento no comprimento da fibra.…”
Section: Resultsunclassified
“…Uncertainty in the amount and timing of precipitation is one of the most serious risks to crop production in the Mississippi Delta. Studies have demonstrated that supplemental irrigation in this humid region could increase crop yield and reduce production risk (Cassel et al, ; Boquet, ; Sui et al, ). Producers in this region have become increasingly reliant on supplemental irrigation to ensure adequate yields.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of water stress immediately after flowering and during the phase of fiber elongation can reduce its length, due to the direct connection with physiological mechanisms of cell expansion (Pettigrew, 2004). Other authors, like Sui et al (2014), claim that increasing irrigation leads to an increase in fiber length.…”
Section: Resultsmentioning
confidence: 99%